Characterization of rabies post‐exposure prophylaxis in a region of the eastern Amazon, state of Pará, Brazil, between 2000 and 2014. (8th February 2018) - De Paula, N. S.; Saraiva, E. A.; Araújo, I. M.; Nascimento, K. K. G.; Xavier, D. A.; Santos, K. S.; Abreu, E. M. N.; Guimãraes, R. J. P. S.; Abel, I.
Summary: Animal bites are a serious public health issue, and prevention strategies have been consistently documented worldwide. The aim of this study was to characterize human anti‐rabies treatment in 11 counties of the Salgado microregion, Pará state, Brazil, which borders the Bragantina microregion, where exposures of human rabies were reported in 2004 and 2005. A descriptive retrospective study was conducted using anti‐rabies treatment notifications registered in the Information System for Notifiable Diseases (SINAN) database of the State Department of Public Health of Pará (SESPA) from January 2000 to December 2014. In this period, 13, 403 exposures were reported, with a growing annual trend ( Y = 68.571 x + 344.96). The years 2012 and 2013 presented the highest exposure incidence. Salinópolis was the county with the highest average annual incidence per 10, 000 persons (62.83), followed by São João de Pirabas (43.28) and São Caetano de Odivelas (41.27). Most patients were males (59.6%) and were 1–19 years old (48.7%). The main species involved in aggressions were dogs (74.1%), followed by bats (13.1%) and cats (7.4%). Biting was the most common kind of exposure, mostly on the lower limbs (39.6%). This study shows that aggression by bats was the second most common cause of demand for the service in the region for the past 14 years. The low quality of records may increase the difficulty of rabies surveillance in Pará.